Crystallization of ZrF4-LaF3-AlF3 glasses - Ribeiro, Sidney J.L. [UNESP]; Goldner, Ph; Auzel, Francois (Elsevier, 1997)
0.7125ZrF4-0.2375(1 - xLaF3 • xLnF3)-0.05AIF3 with x = 0.01, 0.02 and 0.03 for Ln = Er and x = 0.03 for Ln = Pr, Nd glasses were studied by differential thermal analysis (DTA), X-ray diffraction and optical spectroscopy. Avrami parameters (Ec and n) were obtained from DTA curves. With La3+ substitution a decrease in the stability against crystallization was observed. This decrease follows the order Er3+ > Nd3+ ≈ Pr3+ for 3% molar substitution. n values suggest an interface controlled growth mechanism with grain edge nucleation abler saturation. Two crystalline polymorphs of the LaZr3F15 phase were identified. With the substitution of 3 mol% of Pr3+, Nd3+ or Er3+ for La3+ only the crystallization of the rhombohedral α-LnZr3F15 phase was observed. An increase in Ω6 Judd's intensity parameter occurs with crystallization and also an increase in the 1.04 μm peak emission cross-section for Nd3+ 4I3/2 state suggesting the potential application of these glass ceramics in optical amplification devices. © 1997 Elsevier Science B.V.
Keywords: Composition effects; Crystal growth; Crystallization; Differential thermal analysis; Fluorine compounds; Interfaces (materials); Light amplifiers; Nucleation; Spectroscopic analysis; Substitution reactions; X ray crystallography; Avrami parameters; Glass ceramics; Judd's intensity parameters; Optical spectroscopy; Glass